Analisis Faktor-Faktor Psikologis dan Pedagogis dalam Proses Pembelajaran Siswa Kelas XI SMA Webrimata: Motivasi Belajar, Peran Guru, dan Minat Belajar - Sherly Amelia Ledoh; Jacob Abolladaka; Fernando Saragih; Sarah Marselina Otepah; Natalia Desrin Geta Lise (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Learning outcomes serve as an important reference in assessing students’ learning success during the instructional process, particularly in economics subjects. The low achievement of learning outcomes among eleventh-grade students at SMA Negeri Webriamata indicates the need for further research regarding the influence of learning motivation, the teacher’s role, and learning interest on students’ learning outcomes. This study employed a quantitative approach with a causal-associative research design. The population of the study consisted of all ninth-grade students of SMA Negeri Webriamata, totaling 147 students, while the respondents were 85 students selected through purposive sampling based on the lowest examination scores. Data were collected using a questionnaire consisting of twenty-seven statements that had met the instrument testing requirements. Data analysis techniques included the classical assumption test, multiple linear regression analysis, and hypothesis testing. The findings revealed that learning motivation and the teacher’s role had a positive effect on learning outcomes; however, the effect of learning motivation was not statistically significant. Meanwhile, learning interest showed a negative and insignificant effect on students’ learning outcomes.